Mosquito Frequency and Feeding Habits in an Enzootic Canine Dirofilariasis Area in Niterói, State of Rio de Janeiro, Brazil - Labarthe, Norma (1998)
Universidade Federal Fluminense. Centro de Ciências Médicas. Faculdade de Veterinária. Niterói, RJ, Brasil.